From Great Depression to Great Recession : The Elusive Quest for International Policy Cooperation. (International Monetary Fund, 2017)
The global financial crisis and the ensuing Great Recession raised concerns about adjustment fatigue, deflation, currency wars, and secular stagnation that presented a sense of deja vu: similar concerns had arisen at the time of the Great Depression and at the end of World War II. As with earlier crises, these concerns prompted calls for greater international policy cooperation-both to achieve a sustainable recovery from the crisis and to prevent future crises. This volume compiles papers from a 2015 symposium of eminent scholars convened by the IMF to discuss how history can inform current debates about the functioning and challenges of the international monetary system. An introductory chapter sets the stage for the other chapters in the volume by giving a broad overview of the performance of the international monetary system over the past century, highlighting the key events and challenges that shaped it. Subsequent sections look at historical antecedents of today's challenges, describe how the modern international monetary system has been-and continues to be-shaped through international financial diplomacy, provide a present-day perspective, and examine the analytics of international policy coordination.